Scapholunate Ligament Insufficiency in a Patient with Scaphocapitate Coalition - Arenas-Prat, Joan (Journal of Hand and Microsurgery, 2022)
We report a case of chronic scapholunate ligament insufficiency in a patient with scaphocapitate coalition. After more than 4 years of mild symptoms, there was no radiological evidence of progression to scapholunate advanced collapse in spite of minimal load-bearing repetitive physical activities undertaken by the patient as a professional guitarist. We believe that scaphocapitate coalition could contribute to mitigate the progression to scapholunate advanced collapse by preventing abnormal flexion of the scaphoid once the ligament is not competent anymore. The biomechanical and surgical implications of this type of carpal coalition are also discussed.
Keywords: scaphocapitate coalition; scapholunate advanced collapse; scapholunate ligament